ANALISIS KETIDAKADILAN GENDER PADA TOKOH UTAMA DALAM NOVEL YUNI KARYA ADE UBAIDIL SERTA IMPLIKASINYA DALAM PEMBELAJARAN BAHASA INDONESIA - Della Aulia Utami; Wulansari, Fitri; Hajjafiani, Dini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Gender inequality remains a relevant social issue and is frequently represented in literary works. One literary work that addresses this issue is Ade Ubaidil's novel Yuni. This study aims to describe the forms of gender inequality experienced by the main character in Yuni's novel and examine its implications for Indonesian language learning. This study uses a descriptive qualitative approach with text analysis methods and a socialist feminist approach. The research data consist of words, phrases, clauses, and sentences in the novel that depict gender inequality practices. Data collection techniques were conducted through documentary studies, while data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that Yuni experiences various forms of gender inequality, including marginalization, subordination, stereotypes, violence, and workload. This inequality arises as a result of a patriarchal social system that limits women's freedom of movement and freedom. The findings of this study have important implications for Indonesian language learning, particularly as teaching materials for literary appreciation that can foster awareness of gender equality, humanitarian values, and critical thinking skills in students.